ANALISIS PERBANDINGAN LAPORAN KEUANGAN SEBAGAI ALAT EVALUASI PENILAIAN KINERJA PERUSHAAN - Yuli Anwar; Priyo Wismantoro (STIE Binaniaga, 2008)
The Financial Statements are An Extreme Important tool for obtaining information relating to the financial position and result achieved by the company. Financial data will be more meaningful to the parties concerned if the data is compared for two periods or more, and further analyzed to obtain data that will be able to support management decisions will be takenresult of comparative analysis the ratio of 2005 and 2004, indicating financial ratios, namely current ratio, quick ratio and working to total assets ratio increased respectively by 114.12% for the current ratio obtained from difference in current ratio for 2005 and years 2004, decreased 45.33 % for the quick ratio and decreased 2.26 % working ratio to total assets that may be caused by increase in current assets, except cash advances and purchases from the previous year.Ratio of financial operations, which is total debt to equality ratio, and total debt to total assets all increased respectively by 2.51 % and 2.26% are caused by local trade debtsActivity ratio, total asset turnover is increased respectively by 0.56 times and a decrease in accounts receivable turn over to be 8.46 times due increase in sales while the average collection period increased by 40.61 the day due higher average receivables and credit salesProfitability ratios, namely gross profit margin increased by 236.47 % and operating income ratio 280.12 % due the very high increase in sales in 2005, and opeating ratio decreased by 174.07 % due to falling prices of goods sold, net earnings ratio / ROI has increased by 42.08 % total assets rise